John Wycliffe : the morning star - Tew, Tony; Peter Howel (Worcester, PA : Vision Video, 1983)
Dramatic biography of the life of the 14th century scholar and cleric who translated the Bible into English for the first time. Wycliffe found himself in the middle of religious, political and social conflicts. An Oxford scholar, one of Europe's most renowned philosophers, he was a defender of English nationalism against the power of the Pope and a champion of the poor against the injustices of the rich. He taught that God's forgiveness cannot be bought with indulgences. He preached that the only true authority is the Word of God, and the Word could only be understood by all if the people could read it in their native tongue. This feature drama captures the trials and heroic struggles of this significant man of faith, the "Morning star" of the Reformation.
Keywords: Wycliffe, John, 1384-- -- Drama; Great Britain -- Church history -- 1066-1485 -- Drama; Reformation -- Early movements -- Drama